2013
DOI: 10.1136/bmjopen-2013-002971
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of mortality predictors in patients with acute exacerbation of chronic fibrosing interstitial pneumonia

Abstract: ObjectivesTo assess clinical, laboratory and radiographic findings associated with outcomes and to clarify more practical ways to predict hospital mortality in patients with acute exacerbation (AE) of chronic fibrosing interstitial pneumonia (CFIP).DesignSingle-centre retrospective cohort study.SettingUniversity Hospital in Japan.ParticipantsWe identified 51 consecutive patients with AE of idiopathic CFIP through multidisciplinary discussion. Patients who had connective tissue disease, drug-induced lung diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 35 publications
1
39
2
Order By: Relevance
“…In AE IPF, the cohort of 51 patients, as reported by Usui el al., the predictors of mortality were high systemic inflammatory response score and serum procalcitonin levels . However, in our study cohort, those who had significantly lower baseline PaO 2 had higher mortality indicating severe nature of the underlying connective tissue disease.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In AE IPF, the cohort of 51 patients, as reported by Usui el al., the predictors of mortality were high systemic inflammatory response score and serum procalcitonin levels . However, in our study cohort, those who had significantly lower baseline PaO 2 had higher mortality indicating severe nature of the underlying connective tissue disease.…”
Section: Discussioncontrasting
confidence: 53%
“…In patients with AE, this was preceded by upper respiratory in- score and serum procalcitonin levels. 16 However, in our study cohort, those who had significantly lower baseline PaO 2 had higher mortality indicating severe nature of the underlying connective tissue disease.…”
Section: Discussionmentioning
confidence: 51%
“…Higher composite HRCT scores including extent of ground-glass opacification, consolidation, traction bronchiectasis and honeycombing predict mortality [23,29]. Blood-based biomarkers of a worse outcome include elevated lactate dehydrogenase [23,41], C-reactive protein [6], Krebs von den Lungen-6 (KL-6) [29,41], pro-calcitonin [40], circulating fibrocytes [70], elevated interleukin-17 [28] and anti-heat shock protein 70 autoantibodies [39], but none of these have been validated prospectively, or impact clinical decision making. Recently, a staging system for AE with several variables was proposed [41].…”
Section: Influence Of Baseline Prognostic Variablesmentioning
confidence: 99%
“…[1][2][3][4] The phenomenon of acute exacerbation (AE) has been associated with high mortality in IPF, and AEs also seem to cause significant mortality in other FILDs. [5][6][7][8][9][10][11][12][13][14] According to previous studies, every year about 5%-15% of patients with IPF will experience an AE. 5 13 Recently, it was shown that the incidence of AE or death in a study consisting of various types of patients with FILD was 7.8% per year.…”
Section: Introductionmentioning
confidence: 99%